Hydroxyl and calcium ions diffusion from endodontic materials through roots of primary teeth - in vitro study Avaliação in vitro da difusão de íons Ca+2 e OH- de materiais endodônticos em dentes decíduos - Ana Cristina Gerent Petry Nunes; Maria José de Carvalho Rocha (University of São Paulo, 2005)
The purpose of this research was to evaluate the diffusion of calcium (Ca+2) and hydroxyl (OH-) ions from materials with a calcium hydroxide base - Ca(OH)2 through the intact roots of deciduous teeth. This diffusion of ions is important for periapical healing. Forty-six deciduous teeth were selected and instrumented to their working length with #40 files. The teeth were washed during cleaning and shaping with a 1% sodium hypochlorite (NaOCl) solution. The canals were dried with paper points. The teeth were divided into 4 groups based on the sealer type, with 10 specimens in each group. A fifth group of 6 teeth without sealer constituted the control group. The materials used as sealers were: Ca(OH)2 paste associated to propylene glycol (CaPE) thickened at the proportion of 2:1 w/v; UFSC (Federal University of Santa Catarina) paste - a mixture of 0.3g of zinc oxide with 0.3g of Ca(OH)2 with 0.2ml of olive oil 1:1 w/w; Vitapex® and Sealapex®. The coronal access was sealed with a glass ionomer after the root had been filled with each sealer. A one-third apical surface and foramen was hard-pressed with Araldite®. The teeth were stored individually in flasks containing saline solution at 37ºC and 100% humidity. The OH- and Ca+2 ions diffusion levels were determined using a pH meter and an atomic absorption spectrometer. Data were collected at 48 hours and at intervals of 7, 30, 45 and 60 days. Statistical analysis was performed using ANOVA to compare groups. In the pH evaluation, the CaPE group presented the largest OH- ions diffusion, which peaked at sixty days (p=0.0309), when compared to the other groups (p<0.0001). In relation to amount of Ca+2 ions released, the CaPE paste showed the best results, followed by the UFSC's paste. These results suggest that the CaPE paste was the material that allowed the highest diffusion of OH- and Ca+2 ions. O objetivo desta pesquisa foi avaliar a difusão de íons Ca+2 e OH- de materiais endodônticos a base hidróxido de cálcio - Ca(OH)2, através da raiz intacta de dentes decíduos. 46 dentes decíduos foram selecionados e instrumentados em seu comprimento de trabalho até a lima # 40, e irrigados durante o preparo com solução de hipoclorito de sódio 1%, e secos com cones de papel absorvente. Os dentes foram separados em 4 grupos de 10 dentes cada conforme o material obturador, e um grupo controle com 6 dentes permaneceu vazio. Os materiais utilizados como obturadores foram: pasta de Ca(OH)2 associada ao propilenoglicol espessada (CaPE) na proporção de 0,4g de pó para 0,2ml de líquido; pasta UFSC, mistura de 0,3g de pó de óxido de zinco com 0,3g de pó de Ca(OH)2 associado a 0,2ml de óleo de oliva; Vitapex® e Sealapex®. Após a obturação, todos os dentes tiveram o forame e terço apical selado com Araldite® e o acesso coronal selado com ionômero de vidro, permanecendo em frascos individuais com a raiz submersa em solução fisiológica, em estufa a 37ºC em 100% de umidade. A análise da difusão de íons OH- e Ca+2 foi realizada por meio de um pHmetro calibrado e um espectrômetro de absorção atômica, respectivamente, em 48h e em 7, 30, 45 e 60 dias. Conforme o teste estatístico ANOVA para a avaliação do pH, o grupo CaPE apresentou valor estatisticamente significante em relação aos outros grupos (p<0,0001), e a maior difusão de íons OH-, ocorreu em 60 dias (p<0,0309). Em relação a quantidade de íons Ca+2 liberados a pasta CaPE foi a que mostrou melhores resultados, seguida pela pasta UFSC. Conclui-se que a pasta CaPE foi o material obturador que mais difundiu íons OH- e Ca+2.